"No one can ask me 'Why do you take that stuff?'": Men's experiences of antiretroviral treatment in South Africa - (:unkn) unknown (My University, 2010)
This paper examines the way gender shaped the health behaviours, health care experiences and narratives of HIV positive men initiating antiretroviral treatment in South Africa. We conducted participant observation and in-depth, semi-structured interviews with 8 men enrolled in a public HIV treatment programme in a rural health district in KwaZulu Natal. We also interviewed their family members and programme staff. The study found that men's narratives and experiences of ART were complex. Descriptions of control and coping juxtaposed with low self-esteem and guilt. Improvements in health following treatment increased optimism about the future but were readily undermined by men's concerns about being unable to meet strongly gendered expectations in relation to family and work. Alcohol use and abuse by men themselves or by family members was found to be an important issue influencing disclosure, uptake and adherence. Given messages discouraging alcohol use during treatment, men reported self-imposed delays to enrolment while they tried to stop or reduce alcohol use, although none had sought advice or professional help in doing so. Men also felt very threatened by alcohol abuse by family members fearing accidental disclose, insults and violence. With regards to health providers, men held strong views as to appropriate and professional behaviour by programme staff, particularly regarding confidentiality. As ART programmes in Africa become established and evolve, we not only need to identify barriers to men's access and adherence but monitor their health and treatment experiences. These findings suggest that the issue of alcohol and ART warrants further investigation. Additional training for primary health care providers and counsellors on health promotion with men may be useful.
Keywords: African Research